STUDENT'S DIFFICULTIES IN UNDERSTANDING ENGLISH INSTRUCTION IN THE CLASSROOM (INFERENCE: Journal of English Language Teaching, 2026)
Understanding classroom instructions is essential for effective learning in EFL contexts, yet many students face difficulties in comprehending them. This study aims to investigate students’ challenges in understanding English classroom instructions and identify the contributing factors. A descriptive qualitative design was employed, involving five junior high school students in Semarang, Indonesia, selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed four major factors affecting comprehension: instruction delivery, linguistic limitations, classroom environment, and affective conditions. Students struggled with fast-paced and unclear instructions, limited vocabulary, classroom noise, and anxiety when seeking clarification. These findings suggest that effective instructional delivery and supportive classroom environments are crucial for improving students’ understanding. Future research is recommended to involve larger participants and incorporate classroom observations to provide deeper insights into instructional practices in EFL settings.
Keywords: EFL; classroom instruction; vocabulary; comprehension; anxiety